From 0 to 1

Calculus Level 3

If the definite integral x 2 x^{2} t a n 1 x tan^{-1} x with respect to x x from 0 0 to 1 1 can be expressed as π p \frac{\pi}{p} - q r \frac{q}{r} + l n s t \frac{ln s}{t} where gcd (q, r) = 1 and p, q, r, s and t are all positive integers, p + q + r + s + t = ? p + q +r +s + t =?


The answer is 27.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Noel Lo
May 5, 2015

Let x 2 x^2 be d u d x \frac{du}{dx} and t a n 1 x tan^{-1} x be v v . Then u = 1 3 u=\frac{1}{3} x 3 x^3 while d v d x = 1 1 + x 2 \frac{dv}{dx} =\frac{1}{1+ x^2} . Now we get ( 1 3 x 3 ) t a n 1 x (\frac{1}{3}x^3)tan^{-1}x minus the antiderivative of ( 1 3 x 3 ) 1 1 + x 2 (\frac{1}{3}x^3) \frac{1}{1+x^2} . Substituting 1 and 0 into ( 1 3 (\frac{1}{3} x 3 ) ( t a n 1 x ) x^3) (tan^{-1}x) gives us 1 3 ( π 4 ) 0 = π 12 \frac{1}{3}(\frac{\pi}{4})-0 = \frac{\pi}{12}

Now rewrite 1 3 x 3 1 + x 2 \frac{1}{3} \frac{x^3}{1+x^2} as 1 3 ( x x 1 + x 2 ) \frac{1}{3} (x-\frac{x}{1+x^2}) . Integrating this gives us 1 3 [ 1 2 ( x 2 ) 1 2 l n ( 1 + x 2 ) ] = 1 6 [ x 2 l n ( 1 + x 2 ) ] \frac{1}{3} [\frac{1}{2}(x^2) - \frac{1}{2} ln (1+ x^2)] = \frac{1}{6} [x^2 - ln (1+ x^2)] . Substituting 1 and 0 into this gives us 1 6 l n 2 6 0 \frac{1}{6}- \frac{ln 2}{6}-0 .

It follows that the answer is π 12 \frac{\pi}{12} - 1 6 \frac{1}{6} + l n 2 6 \frac{ln 2}{6} and we have 12 + 1 + 6 + 2 + 6 = 27 12 + 1 + 6 + 2 + 6 =\boxed {27} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...